Inventarisasi Arthropoda pada Tanaman Tebu (Saccharum officinarum L.) Di Tiga Umur Tanaman yang Berbeda - Zainal Abidin; Funky Dwy Ushardyna; Arief Lukman Hakim (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Sugarcane (Saccharum officinarum L.) is a national sugar-producing plant. One of the declines in sugar production is caused by pests and diseases and improper control. The study aims to make an inventory of arthropods in sugarcane at the age of 1,5 – 3 months, 4 – 10 months, and < 11 months in order to obtain information on these matters. The research was carried out in three plantation areas in Sumber Perkul, Gedangan, Malang and at the Basic Laboratory of the Universitas Islam Raden Rahmat Malang during March – May 2022. This study used the relative method (Sticky yellow traps, pitfall traps, light traps) and the absolute method (visual control). The results of this 14.932 individu, study obtained 68 families from the Arachnida and Insecta classes, with groups of predatory roles, parasitoids, herbivores and others. The Important Value Index of dominant natural enemies (Parasitoid) Dolichopodidae (45%), Detritivor arthropod (Drosophilidae) and Polinator arthropod (Noctuidae) (26%), Herbivora arthropod Delphacidae (15%), and natural enemies (Predator) Coccinelidae (14%). The conclusion is that from all the calculated indicators there is no group of arthropods that dominates, the diversity is moderate, and the distribution is evenly distributed. There is a change in composition, but in all indicators the calculation of the entire age of the sugarcane plant is still in the stable and balanced category.